Core indicators evaluation of effectiveness of HIV-AIDS preventive-control programmes carried out by nongovernmental organizations. A mixed method study - Mansilla Rosa; Giménez Albert; Romaguera Amparo; Violan Concepció; Pujol-Ribera Enriqueta; Berenguera Anna; Ascaso Carlos; Almeda Jesús (BMC, 2011)
Abstract Background The number of nongovernmental organizations working on AIDS has grown. There is great diversity in the type of activities and population groups that have been targeted. The purposes of this study are: to describe and analyze the objectives and HIV-AIDS preventive activities that are carried out by the AIDS-NGOs that work with AIDS in Catalonia and that receive subsidies from the Department of Health; and to develop a comprehensive proposal for measurable and agreed upon core quality evaluation indicators to monitor and assess those objectives and activities that can have an impact on the fight against inequalities and stigmatization, and incorporate the perspectives of the service providers and users. Methods A mixed method study has been carried out with professionals from the 36 NGOs that work with HIV/AIDS in Catalonia, as well as their users. This study achieved the completeness model using the following phases: 1. A systematic review of AIDS-NGOs annual reports and preparation of a catalogue of activities grouped by objectives, level of prevention and AIDS-NGOs target population; 2. A transversal study through an ad-hoc questionnaire administered to the AIDS-NGOs representatives; 3. A qualitative study with a phenomenological approach through focus groups, individual interviews and observations; 4. Consensus meetings between AIDS-NGOs professionals and the research team using Haddon matrices in order to establish a proposal of evaluation indicators. Results The information was classified according to level of prevention and level of intervention. A total of 248 objectives and 258 prevention activities were identified. 1564 evaluation indicators, addressed to 7 target population groups, were produced. Thirty core activities were selected. The evaluation indicators proposed for these activities were: 76 indicators for 15 primary prevention activities, 43 for 5 secondary prevention activities and 68 for 10 tertiary prevention activities. Conclusions The results could help to homogeneously assess the preventive-control activities carried out of AIDS-NGOs. The proposed indicators could help the professionals to improve the evaluation of the preventive-control AIDS-NGOs activities. Furthermore, the Haddon matrix enables us to identify deficiencies of activities at intervention levels and strategies to bear in mind in order to enhance the future AIDS prevention programs.